2009
DOI: 10.1094/phyto-99-6-0729
|View full text |Cite
|
Sign up to set email alerts
|

Cacopsylla melanoneuraHas No Relevance as Vector of Apple Proliferation in Germany

Abstract: Long-term field surveys on the distribution and natural infection rates of Cacopsylla melanoneura were carried out in commercial and abandoned apple-proliferation-infected orchards throughout Germany, northern Switzerland, and eastern France. Although the infection rates of some orchards reached up to 80%, only 0.09% of all C. melanoneura collected on apple were infected by the pathogen 'Candidatus Phytoplasma mali'. Despite higher population densities, no infected individual was found on wild hawthorn. Indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 44 publications
3
48
1
Order By: Relevance
“…This result was supported by a study from Germany that found the infection rate of C. melanoneura by 'Ca. P. mali' was very low at 0.5-0.6% and the psyllid failed in both acquisition and transmission of this phytoplasma (Mayer et al, 2009).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This result was supported by a study from Germany that found the infection rate of C. melanoneura by 'Ca. P. mali' was very low at 0.5-0.6% and the psyllid failed in both acquisition and transmission of this phytoplasma (Mayer et al, 2009).…”
Section: Discussionmentioning
confidence: 91%
“…In our study, C. picta infection rate was 4.36% and this low rate could be correlated to the low incidence of AP disease in Turkey (Çağlayan et al, 2014). In Germany, the infection rate has been reported as 10% in OW psyllids collected from apple orchards (Mayer et al, 2009) and a high infection rate of 'Ca. P. mali' (40%) in apple trees was detected (Bliefernicht and Krczal, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Cacopsylla melanoneura is considered the main vector of 'Ca. P. mali' in north-western italy (tedeschi and alma 2004), while in other european regions, including South tyrol, transmission trials involving this species did not succeed in infecting healthy test plants (Mayer et al 2009;Wolf et al 2003) or the transmission rate was very low (0.36 %) . in contrast, C. picta was proven to be a highly efficient vector of 'Ca.…”
Section: Molecular Diagnostics Of Plant Pathogensmentioning
confidence: 99%
“…While sap-sucking psyllids are considered crucial for propagation of aP within orchards (Mayer et al 2009), the pathogen can also be transmitted anthropogenically by grafting infected propagation material (Kartte and Seemüller 1988). For this reason, the Molecular Biology laboratory was involved in testing samples taken from propagation and/or nursery material by the Phytosanitary Service of the autonomous Province of Bozen/Bolzano.…”
Section: Testing Of Propagation Materialsmentioning
confidence: 99%
“…in recent years, qualitative and quantitative real-time Pcr approaches have been increasingly used to gain more insight into the epidemiology and pathogenesis of aP (e.g. Baric et al 2008;Bisognin et al 2008;Mayer et al 2009;Musetti et al 2010Musetti et al , 2011rekab et al 2010;Seemüller and Schneider 2007). the protocols for quantitative analysis of 'Ca.…”
Section: Introductionmentioning
confidence: 99%